Gestión de seguridad y salud ocupacional en la Municipalidad Distrital de San Juan Bautista 2023 - Moncada Garcia, Christhiam Jhordam (Universidad Nacional de la Amazonía Peruana, 2024)
The purpose of the study was to make the link between security administration and occupational protection in the District Municipality of San Juan Bautista, 2023. A descriptive-correlational investigation was carried out, with a non experimental design, in which a sample of 152 employees and a questionnaire was applied to collect information. The results indicate that safety management is considered regular (30%) and occupational health is rated equally (30%). Furthermore, a significant correlation was determined between both, demonstrated by a coefficient of 0.830, which is in the range of strong positive correlation, with a bilateral significance of 0.000. Likewise, a relationship is established between the work environment dimension (r=0.702; p = 0.000), and the OHS training dimension (r= 0.687; p = 0.000), for the safety signaling dimension (r= 0.699). ; p = 0.000), the cleaning/maintenance dimension (r= 0.587; p = 0.000), for the common areas (r= 0.674; p = 0.000), finally for the toilet services dimension (r= 0.660; p = 0.000). ) all of them are positively and significantly related to occupational health in the municipality.

El propósito del estudio consistió en realizar la vinculación entre la administración de seguridad y la protección ocupacional en la Municipalidad Distrital de San Juan Bautista, 2023. Se realizó una investigación descriptiva correlacional, con un diseño no experimental, en el que se seleccionó a una muestra de 152 empleados y se les aplicó un cuestionario para recopilar información. Los resultados indican que la gestión de seguridad es considerada regular (30%) y la salud ocupacional es calificada de igual manera (30%). Además, se determinó una correlación significativa entre ambas, demostrada por un coeficiente de 0.830, que se encuentra en el rango de fuerte correlación positiva, con una significancia bilateral de 0.000. Asimismo, se establece una relación entre la dimensión ambiente de trabajo (r=0.702; p = 0.000), y la dimensión capacitación en SSO (r= 0.687; p = 0.000), para la dimensión señalización de seguridad (r= 0. 699; p = 0.000), la dimensión limpieza/mantenimiento (r= 0.587; p = 0.000), para las áreas comunes (r= 0.674; p = 0.000), finalmente para la dimensión los servicios higiénicos (r= 0.660; p = 0.000) todos ellos se relacionan positiva y significativamente con la salud ocupacional en la municipalidad.
Keywords: Gestión de la seguridad; Salud laboral; Municipalidad; https://purl.org/pe-repo/ocde/ford#5.06.02